2021
DOI: 10.1111/jpc.15859
|View full text |Cite
|
Sign up to set email alerts
|

Parechovirus infection in infants: Evidence‐based parental counselling for paediatricians

Abstract: Aim Human parechovirus (HPeV) is an increasingly recognised cause of severe illness and central nervous system infection in infants. Medium‐ to long‐term neurodevelopmental outcomes post‐HPeV infection remain unknown. This study aims to assess neurodevelopmental outcomes for children hospitalised as infants with HPeV infection in their second and third years of life. Methods This prospective cohort study followed children hospitalised with HPeV in Brisbane, Queensland during the 2017/2018 outbreak. Serial appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 24 publications
(71 reference statements)
0
13
0
Order By: Relevance
“…Most studies reported a higher incidence in males (56.4–91%) than in females [ 9 11 , 17 , 21 , 27 , 59 , 60 , 62 , 65 , 66 ]. Only two Korean studies reported a female prevalence (57.1-80%) [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Most studies reported a higher incidence in males (56.4–91%) than in females [ 9 11 , 17 , 21 , 27 , 59 , 60 , 62 , 65 , 66 ]. Only two Korean studies reported a female prevalence (57.1-80%) [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, 15 reports evidenced the presence of seizures [ 1 , 10 , 11 , 21 , 26 , 28 , 45 , 50 , 58 , 62 , 65 68 , 70 ]. Their occurrence may vary from 3.1 to 65.2% [ 10 , 11 , 21 , 26 , 28 , 62 , 65 68 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This included sociodemographic characteristics as well as markers of disease severity [ 9 ] (PICU admission, duration of hospitalization, apnea, seizures, brain magnetic resonance imaging [MRI] results, and developmental assessment after 6 months of age). A subgroup underwent prospective follow-up 1-year postinfection for formal developmental assessment (Ages and Stages Questionnaire) as part of another study [ 18 , 19 ], and these data were included where available.…”
Section: Methodsmentioning
confidence: 99%